Politics of History in China: Constructing the Past, Imaging the Future - B. O. Khubrikov (Международная аналитика)
The article discusses the dynamics and prospects for the development of the historical politics of the PRC at the present stage. The present study attempts to identify two key components of the PRC’s historical politics that define the framework for remembrance in China. The reference points of the study are Chinese interpretations of what should be forgotten or reformatted, as well as the Chinese leadership’s policy of imagining the future. The article is based on the “Resolution on the Major Achievements and Historical Experience of the Party over the Past Century” adopted by the 6th Plenum of the 19th CPC Central Committee, collections of Xi Jinping’s public speeches. In theoretical terms, it relies on the studies of historical politics by A. Assman, A.I. Miller, E. Wolfrum, O.Yu. Malinova. The study demonstrated how the CCP becomes the only mnemonic actor writing its own history. In the first part of the article, forms of “forgetfulness” are considered, behind which there are very different methods, actions and strategies. The second part analyzes the narrative of building the future, expressed in the concepts of “Xiaokang (moderately prosperous society)” and “accelerated promotion of socialist modernization” circulating in Chinese documents as the goal of “two centuries”. In the course of the study, we found that it is in the interests of the CCP, led by Xi Jinping, to present the history of the PRC teleologically, in which the events of the past anticipate the victorious march of the CCP in the history of China. It is for this reason that the main instruments of the historical policy of the PRC are various techniques of oblivion: rewriting, erasing, silence. However, in parallel with the historical policy aimed at the past, the Chinese leadership is also working on images of an imaginary future. Thus, the main goal of China’s historical policy at the present stage is the construction of a single, monolithic, homogeneous story about the past, present and future of the PRC, in which there is no place for discrepancies, criticism and historical nihilism.